(untitled) (Advancements in Homeopathic Research, 2022)
A prospective, study “ Efficacy of homoeopathic medicines in urinary calculi -A single blind, randomised placebo controlled study” conducted by M. N. Homoeopathic Medical College, & Research Institute, Bikaner. The cases were taken from the OPD /IPD from August 2017 to March 2018 to find the usefulness of homoeopathic medicines in cases of Urolithiasis. In this study 200 cases were enrolled and 100 cases were analyzed. Of these, 50 in group A (Homoeopathic medicines) and 50 in group B (Placebo) were analyzed after 6 follow ups. The symptoms pertaining to urolithiasis were assessed before and after treatment. pain, dysuria and haematuria were graded from 0-3 as per severity of complaints. Calculi were graded as per number, size and position of calculi. The difference between the scores were assessed by using SPSS software (ver. 16). The symptom score at baseline and after treatment was analysed and found statistically significant (p= 0.00) decrease in USS in Medicine group (M=5.26, SD= 3.87) than Placebo (M= 9.66, SD= 1.89), t(98)= 7.224, the mean difference between the groups being M= 4.40, SE= 0.61. ( P <0.005). The medicines found most useful were Lycopodium clavatum in 16% (n=08) cases ; Phosphorus in 14% (n=07) cases ; Ber- vul in 12% (n=06) cases ; Nux vomica in 10% (n=05) cases ; Cantharis vesicatoria in 12% (n=06 ) cases and Tabacum in 10% (n=05) cases . Treatment with homoeopathic medicines showed positive response in dissolution/expulsion of calculi. Further validation of these results is needed by conducting randomized clinical trial.